Spatial resolution in electrical impedance tomography: A topical review - Chitturi V.; Farrukh N. (Universitetet i Oslo, 2023)
Electrical impedance tomography (EIT) is a relatively new imaging technique. It has the advantages of low cost, portability, non-invasiveness and is free from radiation effects. So far, this imaging technique has shown satisfactory results in functional imaging. However, it is not yet fully suitable for anatomical imaging due to its poor spatial resolution. In this paper, we review the basic directions of research in the area of the spatial resolution of the EIT systems. The improvements to the hardware and the software developments are highlighted. Finally, possible techniques to enhance the spatial resolution of the EIT systems using array processing beamforming methods are discussed.